Political Communication of the Head of Pugu Village Reviewed from the Perspective of Communicator Structure Patterns, Messages, Channels, Communican and Effect - Atiqah Revalina; Suryanef Suryanef; Al Rafni (Journal of Education Technology Information Social Sciences and Health, 2022)
This article aims to explore and describe how the political communication of the Head of Pugu Semurup Village, Air Warm Barat District, Kerinci Regency was selected from the perspective of Communicator, Message, Channel, Communican and Effect as village head for the period 2021-2027. This type of research uses qualitative research using descriptive methods. Data collection is done through observation and interviews. Research informants were Defrizal and the Success Team, community leaders and Facebook followers of @Pugu Change Movement. The findings of Defrizal's research are using the Facebook media @Pugu Change Movement as a political communication tool so that it differentiates it from other candidates. Judging from the Communicator, Message, Channel, Communican and Effect, it shows Defrizal's political communication, the elected village head namely: first, the Pugu Semurup village head and his team of successes act as a source or communicator. Second, the delivery of political messages to the community, the message was conveyed in the form of a vision and mission by the village head Defrizal and the success team to the community. Third, political communication occurs through mass media or channels, namely the transmission of political communication with primary media in the form of structured words and the use of social media via Facebook. Fourth, the communicator or recipient of the message, namely the community or residents of Pugu Semurup Village as the target of the campaign. Fifth, the effects or consequences arising from the Head of Defrizal Village and the Success Team, namely attracting the attention of the people of Pugu Semurup Village to vote.